2020
DOI: 10.1093/beheco/araa069
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of within-individual variation in extrapair paternity in blue tits (Cyanistes caeruleus) shows low repeatability and little effect of changes in neighborhood

Abstract: Many studies investigated variation in the frequency of extrapair paternity (EPP) among individuals. However, our understanding of within-individual variation in EPP remains limited. Here, we comprehensively investigate variation in EPP at the within-individual level in a population of blue tits (Cyanistes caeruleus). Our study is based on parentage data comprising >10 000 genotyped offspring across 11 breeding seasons. First, we examined the repeatability of the occurrence of EPP, the number of extrapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 98 publications
2
23
0
Order By: Relevance
“…A previous study found no evidence that the proportion of familiar neighbours (i.e. familiar from [26]. Here we examined the associations among individuals that arose during the preceding non-breeding season.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study found no evidence that the proportion of familiar neighbours (i.e. familiar from [26]. Here we examined the associations among individuals that arose during the preceding non-breeding season.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, a social surrounding including many opposite-sex members might favour extra-pair behaviour, and the frequency of social associations could be informative about who will mate with whom [23]. However, the effects of the social environment on patterns of EPP have rarely been investigated, despite potentially being able to give valuable insights into the expression of extra-pair behaviour [23,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sociality functions as an emergent trait of behavioural preference and personality (Aplin et al 2014;Plaza et al 2020). Thus, some individuals are consistently more inclined to socialise than others, as is demonstrated in mammals (Silk et al 2009;Proops et al 2021;Strickland et al 2021) and birds (Croft et al 2009;Aplin et al 2015;Thys et al 2017;Plaza et al 2020;Beck, Valcu, and Kempenaers 2020), but not exclusively (Krause et al 2000;Dimitriadou, Croft & Darden 2019). Sociality is mediated by the social environment, i.e.…”
Section: Introductionmentioning
confidence: 92%
“…Demographic variables are thought to play a central role in shaping genetic mating systems, as the frequency of EPP is expected to be constrained by the distribution and availability of potential mates in both space and time (Westneat and Sherman 1997, Griffith et al 2002, Shuster and Wade 2003). However, there is still no consensus on the general role of demographic variation in driving variation in EPP among individuals and across species (Brouwer and Griffith 2019, Beck et al 2020).…”
Section: Introductionmentioning
confidence: 99%